2013
DOI: 10.4235/jkgs.2013.17.3.152
|View full text |Cite
|
Sign up to set email alerts
|

Successful Fecal Transplantation by Enema for Recurrent and Refractory Clostridium difficile Infection

Abstract: Clostridium difficile infection (CDI) is a common cause of antibiotic-associated diarrhea with an increase in severity and frequency in the recent times. CDI can be refractory and relapses, especially in the elderly or patients with significant comorbidities. Conventional treatments with antibiotics often fail to cure the infection. Even when successfully treated, recurrent infection is common. Some studies have reported that fecal transplantation may be effective and safe for the treatment of recurrent and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…In Korea, the incidence of CDI is also increasing; FMT has been introduced to treat recurrent and refractory CDI [15]. However, there is a lack of research studying the gut microbiota of healthy people and patients with CDI in Korea.…”
Section: Introductionmentioning
confidence: 99%
“…In Korea, the incidence of CDI is also increasing; FMT has been introduced to treat recurrent and refractory CDI [15]. However, there is a lack of research studying the gut microbiota of healthy people and patients with CDI in Korea.…”
Section: Introductionmentioning
confidence: 99%
“…New therapeutic approaches have been investigated for the treatment of recurrent and refractory PMC, and a large number of recent studies have explored the use of FMT. 8 9 10 11 12 13 14 15 The concept of an FMT was first reported in 1958 by Eiseman et al 9 for the treatment of fulminant PMC. Since then, a considerable number of case reports and studies on the treatment's effects and methodologies have been performed worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent randomized control trial, FMT had a better outcome than the use of vancomycin in patients with recurrent and refractory PMC. 8 A domestic study also reported a successful case of treating recurrent and refractory PMC via enema 11 and upper GI endoscopy. 12 This case report was meaningful in that it compared clinical data and colonoscopic findings from follow-up colonoscopies in cases where PMC was managed with colonoscopy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Korea, two cases of severe refractory C. difficile infection treated with fecal transplantation during an initial episode have been reported. One case used esophagogastroduodenoscopy (EGD) while the other case used enema [ 9 10 ]. Here, we report the first case of severe initial C. difficile infection, refractory to antibiotics, that was treated with fecal transplantation using a nasoenteric tube in Korea.…”
Section: Introductionmentioning
confidence: 99%